Guide to the deterioration and failure of building materials - Heckroodt, R. O. (Thomas Telford, 2002)
Professionals concerned with the built environment are all too often confronted with cases where building materials have failed prematurely. This title pulls together in one place information required for the understanding of the causes of such failures, or for the appropriate remedial action.